Marky: a lightweight web tracking tool for document annotation - Pérez-Pérez, Martín (2014)
Document annotation is an elementary task in the development of Text Mining applications, notably in defining the entities and relationships that are relevant to a given domain. Many annotation software tools have been implemented. Some are particular to a Text Mining framework while others are typical stand-alone tools. Regardless, most development efforts were driven to basic functionality, i.e. performing the annotation, and to interface, making sure operation was intuitive and visually appellative. The deployment of large-scale annotation jamborees and projects showed the need for additional features regarding inter- and intra-annotation management. Therefore, this paper presents Marky, a new Web-based document annotation tool that integrates a highly customisable annotation environment with a robust project management system. Novelty lays on the annotation tracking system, which supports per user and per round annotation change tracking and thus, enables automatic annotation correction and agreement analysis.